ROAD SAFETY AND PREVENTION POLICY IN THE UPPER REGION OF NORTHERN THAILAND - Porntumaruk, Petchnapa (Journal of Buddhist Anthropology, 2022)
The Objectives of this research article were to Road Safety and Prevention Policy in the Upper Region of Northern Thailand. The objectives of this study 1) to study the problematic conditions of road safety and prevention policy implementation 2) to study factors and solutions to problems affecting the implementation of road safety and accident prevention policies in the area Upper North of Thailand It is a qualitative research. Key informants representing agencies and network partners in operations related to road safety and accident prevention, namely Chiang Mai, Lampang and Lamphun. The tools used were an in-depth interview form. Analyze data and sifting through it. Descriptive and conclusive the results of the research showed that 1) problems in implementing road safety and accident prevention policies Most of them are motorcycles. There are frequent accidents after 6:00 p.m., most of which are caused by drunk driving and speeding beyond the legal limit. 2) Factors affecting the implementation of safety policies. And the prevention of road accidents, such as the human factor, the law must be strictly and continuously enforced on road users using the road safely. Road factor Inspection of road physical characteristics, risk points, danger points, frequent accident sites. Vehicle Factors that still lack the readiness of basic equipment to use vehicles safely environmental factors traffic barriers both natural obstacles equipment failure As a result, the ability to drive the vehicle is reduced. And law enforcement factors Technology should be used to increase efficiency in law enforcement. And solutions to problems Governments should clearly define the agencies responsible for the prevention and reduction of road accidents. To have sufficient powers, duties and budgets Able to effectively solve the problem of road accidents and people must be aware of their own protection and strictly abide by the law.